ИССЛЕДОВАНИЕ СВОЙСТВ ГЕМОСТАТИЧЕСКИХ МАТЕРИАЛОВ НА ОСНОВЕ ХИТОЗАНАИ НАНОФИБРИЛЛ ХИТИНА - Сущинский, Петр Леонидович; Маевская, Екатерина Николаевна; Федюк, Андрей Михайлович; Рыбинских, Тимофей Сергеевич; Макаров, Александр Юрьевич; Шабунин, Антон Сергеевич; Юдин, Владимир Евгеньевич; Зиновьев, Евгений Владимирович; Дресвянина, Елена Николаевна (Children’s Medicine of the North-West, 2021)